Electron spectroscopy of the main allotropes of carbon1. (19th January 2014) - Kaciulis, S.; Mezzi, A.; Calvani, P.; Trucchi, D. M.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> Recently, carbon spectroscopy became very important due to the growing interest in the applications of new carbon allotropes, especially of 2D structures such as graphene and nanotubes. It is well known that the hybridization of carbon electrons defines most of the properties of these materials. Among the analytical techniques used for the identification of carbon allotropes is the spectroscopy of carbon Auger line, which involves the transitions of valence band electrons and can be excited by electron beam (AES) or X‐ray photons (XAES). From the shape of C KVV spectrum, it is possible not only to recognize the cases of pure sp2 and sp3 configurations but also to quantify their ratio in amorphous carbon films. In present work, an experimental study of three main allotropes of carbon: graphite, diamond, and graphene is reported. The average thickness of graphene was evaluated from the ratio of C 1s and substrate photoelectron peaks, registered at grazing angle. Carbon KVV spectra were investigated by using XAES and AES techniques. Obtained results were compared with the ones acquired for reference samples of graphite and monocrystalline diamond. In addition, some samples of hydrogenated diamond were analyzed. It was demonstrated that the comparison of C KVV spectra excited by electrons and X‐rays can be used for identification of graphene. Diamond‐like C KVV spectrum, observed in XAES experiments, is a very promising fingerprint of graphene. Obtained results are also compared with valence band spectra of graphene, diamonds and graphite that were acquired by using ultraviolet photoemission spectroscopy. Copyright © 2014 John Wiley & Sons, Ltd.